Eleventh Five Year Plan 2007-12 and Annual Plan 2007-08 Orissa Volume-I Government of Orissa - Planning Commission (Planning Commission, 2007)
Orissa is located on the eastern coast, surrounded by Andhra Pradesh, Chhattisgarh, Jharkhand and West Bengal. It has more than 480 km long coastline. It is the 8th largest State with an area of 1,55,707 km2, stands 11th largest in terms of population (36,80 million as per 2001 census), and is 14th with regard to population density (236 persons per km2 in 2001). Despite its rich natural resource endowment, Orissa continues to be very poor. It is regarded as the poorest major State. As per 55th NSS Survey: 1999-2000, about 47.20% population lives below the poverty line, this being the highest headcount ratio among 15 major Indian States. It is predominantly rural and the process of urbanization is very slow. 85.01% people still live in villages, this being the 4th highest only after Bihar, Assam and Himachal Pradesh. Orissa’s per capita annual income was only Rs.7,445 (at 1993-94 prices) in 2005-06, it being the 3rd lowest only above UP and Bihar.
Eleventh Five Year Plan 2007-12 & Annual Plan 2007-08 Orissa Volume-I
Government of Orissa